Banjar Lexicons in The Baayun Anak Tradition: Cultural Meanings and Pedagogical Relevance - Yurianti, Ridha Alifa; Misrita; Ristati (PROJECT (Professional Journal of English Education), 2026)
This study explores the lexicons used in the Baayun tradition of the Banjar community in Banua Halat Village, Tapin Regency, South Kalimantan, and examines their cultural meanings using Ferdinand de Saussure’s semiotic perspective. The study specifically focuses on Banjar lexical items found in Baayun Anak practices, which are preserved in household settings, while Baayun Maulid, performed in religious contexts, employs Arabic religious recitations and does not involve Banjar oral utterances. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews with cultural figures and mothers who have performed the Baayun tradition, and document analysis. The findings reveal that the Banjar lexicons reflect parental hopes, values, and everyday experiences embedded in the tradition. In addition, the study identifies lexicons related to ritual equipment as cultural elements that provide contextual understanding of the Baayun tradition. This research also demonstrates the pedagogical relevance of the findings by illustrating how the Baayun tradition can be utilized as authentic-based material in English Language Teaching, particularly in the form of vocabulary enrichment and procedural texts to support students’ reading and writing skills. The study highlights the importance of integrating local cultural practices into language learning to promote culture-based language teaching.